Keterlekatan (Embeddedness) Tindakan Ekonomi Antara Tukang Kredit Dengan Client Dalam Peminjaman Uang (Studi pada Masyarakat di Jorong Sungai Tarab, Kecamatan Sungai Tarab, Kabupaten Tanah Datar) - Sianturi, Juliana; Zusmelia, Zusmelia; Elvawati, Elvawati (Jurnal Akuntansi Hukum dan Edukasi, 2024)
This study aims to explain the form of embeddedness of economic action between “Tukang Kredit” and clients in lending money to the community in Jorong Sungai Tarab, Kec. Sungai Tarab, Kab Tanah Datar. The approach used is a qualitative approach with a descriptive type. The theory used is Granovetter's theory, namely the concept of embeddedness. The technique of withdrawing informants using purposive sampling technique with the number of informants 14 people. Data collection methods with observation, interviews, and document studies. The unit of analysis is individual. Data analysis used was developed by Miles and Huberman, namely data collection, data reduction, data presentation and conclusion drawing. Based on the results of the study, the embeddedness of economic action between loan sharks and clients in lending money is due to social relationships and social interactions based on personal relationships that last a long time from time to time so that from these economic actions there are the same values, such as exchange and reciprocity, trust, kinship, and social networks so that it can be said to be embeddedness in a relational form, this habit occurs when the perpetrator sees an opportunity to carry out economic action in Jorong Sungai Tarab, Kec. Sungai Tarab.